2018
DOI: 10.1016/j.jde.2018.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior of Boussinesq system of KdV–KdV type

Abstract: This work deals with the local rapid exponential stabilization for a Boussinesq system of KdV-KdV type introduced by J. Bona, M. Chen and J.-C. Saut. This is a model for the motion of small amplitude long waves on the surface of an ideal fluid. Here, we will consider the Boussinesq system of KdV-KdV type posed on a finite domain, with homogeneous Dirichlet-Neumann boundary controls acting at the right end point of the interval. Our goal is to build suitable integral transformations to get a feedback control la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Backstepping with two scalar controls has already been implemented in [13] for a coupled KdV-KdV system with two boundary controls, for which, because of the coupling nature, it is natural to introduce two control terms. More recently, it has been improved in [12], where the authors showed that only one control is sufficient to stabilize the system.…”
Section: Backstepping In Finite Dimensionmentioning
confidence: 99%
“…Backstepping with two scalar controls has already been implemented in [13] for a coupled KdV-KdV system with two boundary controls, for which, because of the coupling nature, it is natural to introduce two control terms. More recently, it has been improved in [12], where the authors showed that only one control is sufficient to stabilize the system.…”
Section: Backstepping In Finite Dimensionmentioning
confidence: 99%
“…Remark 1. Note that the right hand side of (3.4) is well defined for all τ ∈ [0, T ], since ψ xx (0, ·) and ϕ xx (L, ·) belong to H The next result borrowed from [9], with minor changes, gives us the existence and uniqueness of solution for system (3.3). Its proof is presented here for the sake of completeness.…”
Section: Well-posedness: Nonlinear Systemmentioning
confidence: 95%
“…In the present work, we address the problems described in the previous subsection and our main results provide a partial positive answer for the Problems A and B. In order to give an answer for Problem B, we apply the ideas suggested in [9,10], therefore, let us consider…”
mentioning
confidence: 99%
“…To prove the stability of the closed-loop system (1) with the control law (6), we need to show that transformation (2) is bounded and invertible.…”
Section: Stablity Analysis Of the Closed-loop Systemmentioning
confidence: 99%
“…Now it has become an important model. People have carried out a lot of research on the KdV equation, see [1][2] and reference therein. For changing the state of KdV for satisfying our purpose, its control problem is introduced, for example, kinds of stability and controllability results for KdV can be found in [3][4][5][6][7] and reference therein.…”
Section: Introductionmentioning
confidence: 99%